Akurasi Perhitungan 3D Volume Galian Proyek Pembangunan Jalan Tepus-Jerukwudel II Menggunakan GIS - Dafa Prabaswara Wahyudi; Agus Riyanto (Jurnal Manajemen Teknologi & Teknik Sipil, 2023)
Calculation of excavation volume is one of the important activities in earthworks. Volume calculations are still done manually for some projects using Microsoft Office Excel. These calculations are time-consuming and prone to errors. The use of DTM-based 3D models in calculating excavation volume is an important thing that needs to be done for work efficiency. This study aims to determine the accuracy of the 3D-based Digital Terrain Method (DTM) in calculating excavation volume. The data used comes from a topographic survey of 64 points. Volume calculations were performed using the 2D Average End Area and 3D DTM-based methods (TIN and Kriging) using ArcGIS. The calculation results will be compared with the actual data from the project excavation volume report. The results show that the 3D volume calculation has fairly good accuracy compared to the traditional average end area method, with a difference of 1.01%. TIN can represent the results of the calculation of the excavation volume, which is quite good, with a difference of 1.33% to the actual volume and RMSE 107.49 m3. This is because the land surface under review is a mountainous area, where the formed surface tends to be uneven, and elevation changes sharply. This is in accordance with the characteristics of the DTM formed by TIN. So the selection of the most appropriate surface modeling method in mountainous areas is TIN. Using the TIN method can minimize the difference in volume calculations and increase the accuracy of soil volume calculations.